1971
DOI: 10.1055/s-0028-1094169
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Pituitary "Fettstoffwechselhormon" - IV. Comparisons Between the Lipolytic Activity of ACTH and Some Fractions of Porcine Pituitaries In Vitro

Abstract: Tbe lipolytic activity of some fractions isolated from porcine pituitary glands was studied in vitro on isolated rat fat tissue. As the check.ed fractions showed cortiootropic activity also, their lipolytic effect was oompared with that of ACfIl For the pituitary gland fraction with the highest lipolytic efTect it oould be shown that tbis lipolytic activity was not due or only to a small extent due to a oontamination with ACfH.Horm. Metab. Res. 3: 167-170 (1971) K e y -W 0 r d s: Lipolytic Hormone -Adrenoco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1972
1972
1977
1977

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…The peptides P-LF I, P-LF 11, and P-LF III isolated from fraction P N by gel chromatography (Schleyer et al 1970) were also lipolytically active in vitro (Schleyer et al 1971). Examinations on disc electrophoresis at pH 9 (tris-hydrochloric acid-buffer) showed that these substances were still composed of several fractions.…”
Section: Methodsmentioning
confidence: 94%
See 2 more Smart Citations
“…The peptides P-LF I, P-LF 11, and P-LF III isolated from fraction P N by gel chromatography (Schleyer et al 1970) were also lipolytically active in vitro (Schleyer et al 1971). Examinations on disc electrophoresis at pH 9 (tris-hydrochloric acid-buffer) showed that these substances were still composed of several fractions.…”
Section: Methodsmentioning
confidence: 94%
“…The fractions eluated from CM-cellulose were lyophilized and fina\1y desalted on Sephadex G 25 medium (40 x 2,5 cm) with 0.1 N acetic acid as eluan t. The lipolytic activity of the P-LF -fractions was tested on isolated rat fat tissue according to a method described recently (Schleyer et al 1971). The corticotropie activity was measured with a radioimmunological method (Voigt, Fehm and Pfeiffer 1971).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation